TiO2/graphitic carbon nitride nanosheet composite with enhanced sensitivity to atmospheric water - Tosapol Maluangnont; Phieraya Pulphol; Satana Pongampai; Thawanrat Kobkeatthawin; Siwaporn Meejoo Smith; Naratip Vittayakorn (My University, 2023)
The TiO 2 /CNNS composite shows enhanced sensitivity to atmospheric water ( i.e. , varied impedance with exposure to air during the measurement) compared to CNNS.
Keywords: Nanosheet; Graphitic carbon nitride; Carbon fibers; Gas Sensing Nanomaterials and Sensors